Left Atrial Improvement in Patients With Secondary Mitral Regurgitation and Heart Failure : The COAPT Trial - Pio Stephan M.; Medvedofsky Diego; Delgado Victoria; Stassen Jan; Weissman Neil J.; Grayburn Paul A.; Kar Saibal; Lim D. Scott; Redfors Björn; Snyder Clayton; Zhou Zhipeng; Alu Maria C.; et al. (American College of Cardiology Foundation, 2026)
Background: Functional mitral regurgitation induces adverse effects on the left ventricle and the left atrium. Left atrial (LA) dilatation and reduced LA strain are associated with poor outcomes in heart failure (HF). Transcatheter edge-to-edge repair (TEER) of the mitral valve reduces heart failure hospitalization (HFH) and all-cause death in selected HF patients.
Objectives: The aim of this study was to evaluate the impact of LA strain improvement 6 months after TEER on the outcomes of patients enrolled in the COAPT (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation) trial.
Methods: The difference in LA strain between baseline and the 6-month follow-up was calculated. Patients with at least a 15% improvement in LA strain were labeled as "LA strain improvers." All-cause death and HFH were assessed between the 6 and 24-month follow-up.
Results: Among 347 patients (mean age 71 ± 12 years, 63% male), 106 (30.5%) showed improvement of LA strain at the 6-month follow-up (64 [60.4%] from the TEER + guideline-directed medical therapy [GDMT] group and 42 [39.6%] from the GDMT alone group). An improvement in LA strain was significantly associated with a reduction in the composite of death or HFH between the 6-month and 24-month follow-up, with a similar risk reduction in both treatment arms (Pinteraction = 0.27). In multivariable analyses, LA strain improvement remained independently associated with a lower risk of the primary composite endpoint both as a continuous variable (adjusted HR: 0.94 [95% CI: 0.89-1.00]; P = 0.03) and as a dichotomous variable (adjusted HR: 0.49 [95% CI: 0.27-0.89]; P = 0.02). The best outcomes were observed in patients treated with TEER in whom LA strain improved.
Conclusions: In symptomatic HF patients with severe mitral regurgitation, improved LA strain at the 6-month follow-up is associated with subsequently lower rates of the composite endpoint of all-cause mortality or HFH, both after TEER and GDMT alone. (Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients With Functional Mitral Regurgitation [COAPT]; NCT01626079)